Fine Motor Skills Through the Use of Learning Technologies and Knowledge Based on Bloom's Taxonomy (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2021)
The purpose of the research experience was to improve fine motor skills using the new TAC Knowledge and Learning Technologies, based on Bloom's taxonomy in first grade children at the Blanca Durán de Padilla school. His methodology was classroom action research (IAA). The population under study 1 teacher and 31 student. For this, a way forward was envisioned that consisted of identifying the fine motor degree, carrying out a documentary scan that could specify theories to address the issue in question, It is concluded that applying digital educational resources strengthens fine motor skills and contributes to the integral development of the infant
Keywords: fine motor skills; didactic strategy; TAC and Bloom's taxonomy